2016
DOI: 10.1063/1.4966664
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nitrogen content and vacancies on structure and mechanical properties of Mo–N thin films

Abstract: Based on a combined computational and experimental study, we show that besides the thermodynamically stable β-MoN0.5 and δ2-MoN phases, also metastable γ-MoNx and its ordered relative γ′-MoNx can be synthesized by physical vapor deposition. The formation of the NaCl-based γ-MoNx phase is favored for nitrogen concentrations between 23 and 34 at.% (i.e., x = 0.30–0.53). Higher nitrogen contents (close to the 3:2 stoichiometry, hence, MoN0.67) favor the ordering of the vacancies at the nitrogen sublattice (hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 48 publications
7
34
1
1
Order By: Relevance
“…It is observed that at large compressive stress the values of H and E are higher than the values at lower stress state, whereas the penetration of the indenter decreases. These values are smaller than those reported for γ-Mo 2 N coatings deposited on stainless steel substrates (23 GPa and 290 GPa for H and E respectively) [43] or a hardness of 33 GPa reported for sputtered cubic MoN 0.53 [42,53]. We can explain this by the changes in the bonding energy in the films when the nitrogen concentration increases.…”
Section: Hardness and Elastic Moduluscontrasting
confidence: 65%
See 1 more Smart Citation
“…It is observed that at large compressive stress the values of H and E are higher than the values at lower stress state, whereas the penetration of the indenter decreases. These values are smaller than those reported for γ-Mo 2 N coatings deposited on stainless steel substrates (23 GPa and 290 GPa for H and E respectively) [43] or a hardness of 33 GPa reported for sputtered cubic MoN 0.53 [42,53]. We can explain this by the changes in the bonding energy in the films when the nitrogen concentration increases.…”
Section: Hardness and Elastic Moduluscontrasting
confidence: 65%
“…The atomic ratio N/Mo into the films obtained is higher than the N/Mo ratio in γ-Mo 2 N structure (0.5), this indicates incorporation of excess nitrogen in the otherwise unfilled octahedral interstitial sites of the γ-Mo 2 N structure [25,38]. In recent studies of Mo-N films [42], γ-MoN x phase was prepared with nitrogen partial pressure to total pressure ratios, P N2 /P T between 0.2 and 0.32 with the content of nitrogen in γ-MoN x phases in the range of x = 0.30-0.53 and crystallized in single-phase cubic-structure. The critical nitrogen concentrations for the Mo to γ-Mo 2 N phase transition varied from author to author [38,43].…”
Section: Films Compositionmentioning
confidence: 81%
“…Despite being metastable, the cubic modifications of MoN and TaN (Fm3m, #225), referred to as rocksalt structure (rs), have been synthesized using nonequilibrium growth techniques such as reactive magnetron sputtering in high nitrogen partial pressure atmosphere, nitrogen ion implantation, or low energy ion assisted deposition 14,[23][24][25][26][27][28][29] . Importantly, some properties of the metastable cubic variants are comparable with, or even superior to those of the ground state phases, e.g., cubic TaN prepared by shock and static compression was shown to have very good high-temperature stability comparable to that of the hexagonal WC-type phase 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Увеличенный период, характерный для γ-Mo 2 N с более чем на 80% заполненными октаэдрическими междоузлиями, наблюдался в вакуумно-дуговых покрытиях ранее в случае формирования системы Mo−N при P N > 2 mTorr и низком потенциале смещения [13,14]. Система была детально проанализирована (как неравновесная фаза MoN с решеткой типа NaCl) в работе [15].…”
Section: поступило в редакцию 28 августа 2017 гunclassified